P059 Acceptability of remote consulting during COVID-19 among patients with two common long-term musculoskeletal conditions: findings from three qualitative studies and recommendations for practice. (23rd April 2022) - Paskins, Zoe; Bullock, Laurna; Manning, Fay; Bishop, Simon; Campbell, Paul; Cottrell, Elizabeth; Jinks, Clare; Narayanasamy, Melanie; Scott, Ian; Sahota, Opinder; Ryan, Sarah
Abstract: Background/Aims: The COVID-19 pandemic led to the widespread adoption of remote consultations. Whilst remote consultations offer many potential advantages to patients and healthcare services, they are unlikely to be suitable for all. Guidance encourages clinicians to consider patient preferences when choosing face-to-face vs remote consultations. However, little is known about acceptability of, and preferences for remote consultations, particularly amongst patients with musculoskeletal conditions. This study aimed to explore the acceptability of, and preferences for, remote consultations among patients with osteoporosis and rheumatoid arthritis. Methods: Data for this study derived from three UK qualitative studies: iFraP (improving fracture prevention study), Blast Off (BO; Bisphosphonate aLternAtive regimenS for the prevenTion of Osteoporotic Fragility Fractures), and ERA (Exploring people with Rheumatoid Arthritis' experience of the pandemic). Each study explored patient experiences of accessing and receiving healthcare during the pandemic year. Transcripts from each data set relating to remote consulting were extracted. A minimum of two study team members worked independently, following a consistent approach, to conduct a rapid deductive analysis using the Theoretical Framework of Acceptability (TFA). The TFA consists of 7 constructs to understand acceptability of, in this context, remote consultations, including: affective attitudes; intervention coherence; perceived effectiveness; burden; self-efficacy; opportunity-costs; and ethicality . Following coding, the findings of all three studies were pooled. Analysis was facilitated by group meetings to discuss interpretations. Results: Findings from 1 focus group and 64 interviews with 35 people, who had mostly experienced telephone consultations, were included the analysis. Participants' emotional attitudes to remote consultations, views on fairness ( ethicality ) and sense making ( intervention coherence ) varied according to their specific needs for the consultation and values, relative to the pandemic context; participants perceived remote consultations as making more sense and being 'fairer' earlier in the pandemic. Some participants valued the reduced burden associated with remote consultations, while others highly valued, and did not want to give up, non-verbal communication or physical examination associated with face-to-face consults ( opportunity costs ); although perceived need for physical examination in participants with RA was associated with strong preference for face-to-face consultations, asymptomatic participants with RA and osteoporosis also expressed similar strong preferences. Some participants described low confidence ( self-efficacy ) in being able to communicate in remote consultations and others perceived remote consultations as in effective, in part due to suboptimal communication. Conclusion: Acceptability of, and preferences for remote consultation appear to be influenced by a range of societal, healthcare provider and personal factors and in this study, were not fixed, or condition-dependent. Remote care by default has the potential to exacerbate health inequalities and needs nuanced implementation. The findings have supported the development of patient-centred recommendations for practice that should be considered alongside clinician-focused recommendations when deciding whether remote consultations are appropriate. Disclosure: Z. Paskins: Grants/research support; NIHR, Clinician Scientist Award (CS-2018-18-ST2-010)/NIHR Academy. L. Bullock: None. F. Manning: Grants/research support; part funded NIHR Clinical Research Network Scholar Programme. S. Bishop: None. P. Campbell: None. E. Cottrell: None. C. Jinks: Grants/research support; part funded by the NIHR Applied Research Collaboration (ARC) West Midlands. M. Narayanasamy: None. I. Scott: Grants/research support; funded by an NIHR Advanced Research Fellowship Award (NIHR300826). O. Sahota: None. S. Ryan: None.